Gigant Transethmoidal Meningoencephalocele Operated by Full Endonasal Endoscopic Approach: Case Report - Omar Lopez Arbolay; Jorge Rojas Manresa; Justo Gonzalez Gonzalez; Jose Luis Bretón Rosario (Case Reports in Medicine)
Intranasal meningoencephaloceles have historically been managed by neurosurgeons, although their main clinical manifestations are rhinological. Recent advances in endoscopic skull base surgery has significantly improved the treatment of these lesions and consequently diminished appreciable surgical morbidity. We report an ethmoidal meningoencephalocele case operated on by endonasal endoscopic approach for removal of the lesion and reconstructing the associated skull base. From this experience, we conclude that removal of the lesion and watertight closure of the skull base irrespective of the size of the mass and anterior skull base defect are the operation’s most important aspects.